MODEL SOLIDARITAS SOSIAL ORGANISASI PEREMPUANDI ERA PANDEMI COVID-19 - Yusuf Adam Hilman; Eli Purwati (Universitas Djuanda Bogor, 2022)
Social solidarity in women's organizations is something unique to study, when collective awareness declines due to the ongoing COVID-19 pandemic, This study seeks to see the model of solidarity that is formed within the organization. This research is descriptive qualitative, with primary and secondary data sources. The results of this study show that the type of solidarity that is formed is organic solidarity, which occurs in modern times, with a high division of work specialization, and a dominant individualistic nature. Organizational values ​​are one of the important things that drive the emergence of collective consciousness, which then collects donations through the ta'awun or urunan model, for people affected by COVID-19.